Syair Kisah Engku Puteri: The Concept of Moral Leadership in the Tradition of Historiography (Melayu: Jurnal Antarabangsa Dunia Melayu, 2025)
In discussing the concept of moral leadership as an essential force within the Malay historiographical tradition, this study focuses on Syair Kisah Engku Puteri, authored by Engku Haji Ahmad. The work narrates the life journey of Engku Puteri Raja Hamidah, the consort of Sultan Mahmud Riayat Syah, who has rarely been the focus of scholarly research. As the custodian of the Riau Kingdom’s regalia, Engku Puteri Raja Hamidah exemplifies noble moral leadership, demonstrated by her efforts to defend the sovereignty of the Riau Kingdom from colonial encroachment. Hence, this research aims to explore the extent to which moral leadership plays a crucial role in shaping the character of a leader. This study adopts a qualitative research design, utilising a library research method. The analysis of moral leadership is conducted based on al-Ghazali’s (2013) framework, drawing upon specific events depicted in Syair Kisah Engku Puteri. Four main aspects of noble moral leadership qualities are clearly recorded in the literary work: virtues ingrained within the soul, inherent goodness that operates without the need for rational deliberation, moral virtues in accordance with the Quran and Sunnah, and dispositions that abstain from actions deemed immoral or improper based on the framework of the Quran and Sunnah. Thus, the concept of moral leadership highlighted in this historiographical tradition paves the way for further research into the capabilities and roles of leaders, be they Sultans or consorts, within the context of Malay historiography.Full text: PDF